2019
DOI: 10.4236/psych.2019.1011093
|View full text |Cite
|
Sign up to set email alerts
|

The Person-in-the-Rain Drawing Test as an Assessment of Soldiers’ Army Life Adjustment and Resilience

Abstract: This quantitative study investigated the applicability of the Person-in-the-Rain drawing test (PITR) as a psychological evaluation tool to assess individuals' psychological capacity to deal with stress. The subjects of the study were 300 soldiers from three army units. The study's research tools included the PITR, the Army Life Adjustment Scale, and the Resilience Scale. The study's findings are as follows. First, there was a significant difference in both the Resource subtotal and the Coping capacity score wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…There was a significant correlation between the Coping Capacity Score and unit cohesion, while the Stress Score in this study exhibited no significant correlations with unit cohesion. Previous investigators found similar results indicating that the Stress Score showed lower explanatory power than other PITR scores (Jue & Ha, 2019b;Kwon, Kim, & Song, 2016). When examining the relationship between self-efficacy and the PITR among nurses, significant differences were observed in the PITR resource scores according to the amount of self-efficacy, but no difference was found for the PITR stress scores (Kwon, Kim, & Song, 2016).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…There was a significant correlation between the Coping Capacity Score and unit cohesion, while the Stress Score in this study exhibited no significant correlations with unit cohesion. Previous investigators found similar results indicating that the Stress Score showed lower explanatory power than other PITR scores (Jue & Ha, 2019b;Kwon, Kim, & Song, 2016). When examining the relationship between self-efficacy and the PITR among nurses, significant differences were observed in the PITR resource scores according to the amount of self-efficacy, but no difference was found for the PITR stress scores (Kwon, Kim, & Song, 2016).…”
Section: Discussionmentioning
confidence: 53%
“…When examining the relationship between self-efficacy and the PITR among nurses, significant differences were observed in the PITR resource scores according to the amount of self-efficacy, but no difference was found for the PITR stress scores (Kwon, Kim, & Song, 2016). Jue and Ha (2019b), who conducted the PITR among conscript soldiers, found that soldiers with high military life adjustment showed greater coping capacity and presence of more resources on the PITR, but no differences were observed in the PITR stress scores between the high and low mili-tary adjustment groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine the characteristics, level and components of resiliency, an empirical study was conducted using "The Person-in-the-Rain Drawing" technique (Jue, J., Ha, J., 2019). Respondents are the representatives of those Ukrainians who managed to stay in Kyiv during the severe military operations in February-April 2022.…”
Section: Methodsmentioning
confidence: 99%
“…Source: Jue and Ha (2019) According to the results of the study of the "The Person-in-the-Rain Drawing" methodology, it can be stated that the majority of respondents demonstrate an average level of resistance and confrontation in adverse situations (Fig. 1).…”
Section: A Person's Mood Emotions and Experiencesmentioning
confidence: 99%